Compulsivity is measurable across distinct psychiatric symptom domains and is associated with familial risk and reward-related attentional capture. (24th August 2020) - Albertella, Lucy; Chamberlain, Samuel R.; Le Pelley, Mike E.; Greenwood, Lisa-Marie; Lee, Rico SC; Den Ouden, Lauren; Segrave, Rebecca A.; Grant, Jon E.; Yücel, Murat
Abstract: Background: Compulsivity can be seen across various mental health conditions and refers to a tendency toward repetitive habitual acts that are persistent and functionally impairing. Compulsivity involves dysfunctional reward-related circuitry and is thought to be significantly heritable. Despite this, its measurement from a transdiagnostic perspective has received only scant research attention. Here we examine both the psychometric properties of a recently developed compulsivity scale, as well as its relationship with compulsive symptoms, familial risk, and reward-related attentional capture. Methods: Two-hundred and sixty individuals participated in the study (mean age = 36.0 [SD = 10.8] years; 60.0% male) and completed the Cambridge-Chicago Compulsivity Trait Scale (CHI-T), along with measures of psychiatric symptoms and family history thereof. Participants also completed a task designed to measure reward-related attentional capture ( n  = 177). Results: CHI-T total scores had a normal distribution and acceptable Cronbach's alpha (0.84). CHI-T total scores correlated significantly and positively (all p  < 0.05, Bonferroni corrected) with Problematic Usage of the Internet, disordered gambling, obsessive-compulsive symptoms, alcohol misuse, and disordered eating. The scale was correlated significantly with history of addiction and obsessive-compulsive related disorders in first-degree relatives of participants and greater reward-related attentional capture. Conclusions: These findings suggest that the CHI-T is suitable for use in online studies and constitutes a transdiagnostic marker for a range of compulsive symptoms, their familial loading, and related cognitive markers. Future work should more extensively investigate the scale in normative and clinical cohorts, and the role of value-modulated attentional capture across compulsive disorders.